2021
DOI: 10.2169/internalmedicine.7119-21
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Central Venous Catheter Use in the Hematology Unit with the Introduction of Ultrasound Guidance and a Peripherally Inserted Central Venous Catheter

Abstract: Objective A central venous catheter (CVC) is often needed to treat hematologic diseases, but it is accompanied by many complications. Ultrasound guidance (USG) or a peripherally inserted central venous catheter (PICC) can reduce such complications. Meterials We collected data of patients with attempted CVC placement in our hematology unit in 2012 (before introduction of USG and PICC) and 2018 (after introduction) and compared both periods. Results In total, 187 CVC insertions were attempted in 2018 and 198 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Peripherally inserted central venous catheters is expected to improve patient safety and has been widely used as an alternative to CICC in hospitalized patients ( 4 ). A meta-analysis comparing PICC with CICC demonstrated that PICC was associated with a lower risk of bloodstream infection ( 41 ); however, most trials were observational studies and only one RCT was included in this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripherally inserted central venous catheters is expected to improve patient safety and has been widely used as an alternative to CICC in hospitalized patients ( 4 ). A meta-analysis comparing PICC with CICC demonstrated that PICC was associated with a lower risk of bloodstream infection ( 41 ); however, most trials were observational studies and only one RCT was included in this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomic site chosen for CICC placement, including the jugular, subclavian, and femoral veins, influences the risk and type of complications ( 3 ). Recently, peripherally inserted central venous catheters (PICC) have been used as substitutes for CICC in an increasing number of hospitalized patients ( 4 ).…”
Section: Introductionmentioning
confidence: 99%